BRIDGING EMOTIONAL INTELLIGENCEAND ENTREPRENEURIAL SUCCESS: A DATA-DRIVEN STUDY IN EMERGING ECONOMIES (Lex localis - Journal of Local Self-Government, 2025)
The future may be AI-driven, but the present belongs to EI-powered minds.Entrepreneurial landscapes today are not only navigated by strategies and skills, but also by the silent strength of EI.Emotional intelligence (EI) plays a vital role in determining entrepreneurial success (ES)in today's competitive and challenging business environment. The existing literature underscores the significance of cognitive and technical skills for entrepreneurship, but there is a lack of empirical research on the clear, measurable impact of EI on entrepreneurship, particularly in emerging economies. This study aims to fill that gap by exploring the effects of different components of EI—self-awareness, self-regulation, motivation, empathy and social skills—on ES, including business growth, innovation and resilience, through statistical methods.A sample of 150 corporate entrepreneurs from various sectors completed a structured questionnaire and the responses were analysed using multiple regression and Pearson’s correlation techniques to examine the strength and significance of relationships. Overall, EI was found to be positively related to ES, with motivation and self-regulation showing the strongest relationships. Entrepreneurs high in EI also demonstrated greater adaptability, customer orientation and team management skills than others.The study’s takeaway is twofold: first, it supports including EI in entrepreneurship training programs; second, it provides investors and incubators with evidence-based reasons to evaluate EI scientifically. These findings add to the growing evidence that EI is more than just a soft skill—it is a strategic asset that can be leveraged for sustainable entrepreneurial success.